The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.14202/vetworld.2020.1581-1587
|View full text |Cite
|
Sign up to set email alerts
|

Description of normal head structures of the one-humped camel (Camelus dromedarius) by magnetic resonance imaging, computed tomography, and cross-sectional anatomy

Abstract: Aim: This study was designed for the 1st time to describe the normal head structures of one-humped camel (Camelus dromedarius) using both magnetic resonance imaging (MRI) and computed tomography (CT) as well as cross-sectional anatomy. Materials and Methods: Five fresh cadaver heads were collected from clinically normal camels and then subjected to T1-weighted MR and CT imaging. Afterward, these examined heads were transversely sliced to obtain seven crossing levels. Results: The obtained structures per each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…On the other hand, several studies examined several other camel cadaver organs, including the kidneys, adrenal glands, and vallate papillae, morphometrically [16,17]. MRI, as beneficial diagnostic imaging, was used in the assessment of camel tarsus [18][19][20], normal brain [21,22], standard head [7,9], and normal testes and epididymis [23]. Histological, radiological, and ultrasonographic studies have also examined camel cadaveric parts [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, several studies examined several other camel cadaver organs, including the kidneys, adrenal glands, and vallate papillae, morphometrically [16,17]. MRI, as beneficial diagnostic imaging, was used in the assessment of camel tarsus [18][19][20], normal brain [21,22], standard head [7,9], and normal testes and epididymis [23]. Histological, radiological, and ultrasonographic studies have also examined camel cadaveric parts [23].…”
Section: Discussionmentioning
confidence: 99%
“…Performing MRI on large animals is technically challenging due to the lack of sufficient magnetom fittings for these animals [7,8]. This limitation has resulted in the application and interpretation of MR images of large animals, such as horses, cattle, and camels, being restricted to examining cadavers [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…described the extension of the maxillary sinus from the P 2 to the M 3 in buffaloes. In camels, the rostral border of the maxillary sinus extends to the P 3 or P 2 ‐M 1 15 . On the other hand, variable extensions have been found, such as from the P 2 to the zygomatic and lacrimal bones in small ruminants, 4 from the P 2 to the M 3 in goats, 19 and from the P 2−3 to the lacrimal bulla in sheep 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…In camels, the rostral border of the maxillary sinus extends to the P 3 or P 2 -M 1 . 15 On the other hand, variable extensions have been found, such as from the P 2 to the zygomatic and lacrimal bones in small ruminants, 4 from the P 2 to the M 3 in goats, 19 and from the P 2−3 to the lacrimal bulla in sheep. 17,18 In this study, we found that the rostral tip was at the P 3 level in eight cows and the P 2 level in four cows (Figure 1C-D/MS) and extended caudally to the lacrimal bulla, the maxillary tuberosity, and the zygomatic bone (Figures 2-4,7/MS).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation